IMPLEMENTASI PENGUATAN PENDIDIKAN KARAKTER BERBASIS BUDAYA SEKOLAH - Jhon Elias Dubu; Yulius Mataputun; Urip Wahyudin; Indah Slamet Budiarti; Kusdianto Kusdianto; Ida Mariati Hutabarat (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
The implementation of Character Education Strengthening in remote areas is often hampered by geographic isolation and extreme limitations in physical facilities. This study focuses on the strategy of internalizing character values ​​through school culture at SD Inpres Malagai, Lanny Jaya Regency, Papua Mountains. The research steps used a qualitative approach with a case study design through data collection techniques in the form of participatory observation, in-depth interviews, and documentation of eleven key informants. Data were analyzed interactively including the stages of reduction, presentation, and systematic conclusion drawing. The research findings show that although the institution operates with a minimal ratio of only eight educators to serve 249 students without electricity, character formation continues to be effective through the method of teacher role models as a living curriculum. Religious values, integrity, and mutual cooperation have been successfully integrated harmoniously with the local wisdom of the Lani Tribe. Quantitatively, the limited learning space with only two units remaining in good condition does not hinder the routine of ten minutes of literacy before learning, although extracurricular activities are still hampered by regional security risks. The main conclusion of this study confirms that the strength of social capital and personal dedication of educators in the concept of resilience pedagogy is able to overcome infrastructure barriers in marginal areas to produce a generation of integrity without relying on modern technological facilities.